2019
DOI: 10.1049/iet-ipr.2018.6120
|View full text |Cite
|
Sign up to set email alerts
|

Prediction error expansion‐based reversible data hiding in encrypted images with public key cryptosystem

Abstract: Advances in signal processing in the encrypted domain and cloud computing have given rise to privacy‐preserving technologies. In recent years, reversible data hiding in encrypted images (RDH‐EI) has received attention from the research community because additional data can be embedded into an encrypted image without accessing its original content, and the encrypted image can be losslessly recovered after extracting the embedded data. Although the recent development of RDH‐EI compatible with homomorphic public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…where μ ∈ (0, 1) represents the control parameter. In this work, the control parameter μ and the initial value y 0 ∈ [0, 1] are used as the keys for controlling the random sequence c by iteratively repeating the Equation (1). It is reported that the total combinations of μ and y 0 for the skew tent map is 2 104 [36], which is a large key space against the brute-force attacks [37,38].…”
Section: Image Encryptionmentioning
confidence: 99%
See 1 more Smart Citation
“…where μ ∈ (0, 1) represents the control parameter. In this work, the control parameter μ and the initial value y 0 ∈ [0, 1] are used as the keys for controlling the random sequence c by iteratively repeating the Equation (1). It is reported that the total combinations of μ and y 0 for the skew tent map is 2 104 [36], which is a large key space against the brute-force attacks [37,38].…”
Section: Image Encryptionmentioning
confidence: 99%
“…Therefore, data security has attracted much attention in the past years. Reversible data hiding (RDH) [1][2][3][4] is a useful technique of data security. It can embed secret information into multimedia carrier, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They cannot identify the privacy sensitivity differences among instances in an image. Inspired by the fact that the problem of differential privacy has been considered in the field of data processing [21,22], we believe it is necessary to measure the privacy levels of the instances in an image. And it is valuable to research the contribution of visual information on the privacy measurement.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, reversible data hiding (RDH) [2] is introduced, which can ensure the privacy and extractability of embedded information, and can completely recover the cover medium without damage. Nowadays, many RDH algorithms are proposed, including lossless compression [3][4][5][6], histogram shifting (HS) [7][8][9][10], difference expansion (DE) [11] and prediction error expansion (PEE) [12][13][14][15] and so on. The main idea of compression is loss-less compression of the content of the cover medium, such as the least significant bit (LSB) and embed secret information in the space saved.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many RDH algorithms are proposed, including lossless compression [3][4][5][6], histogram shifting (HS) [7][8][9][10], difference expansion (DE) [11] and prediction error expansion (PEE) [12][13][14][15] and so on. The main idea of compression is loss-less compression of the content of the cover medium, such as the least significant bit (LSB) and embed secret information in the space saved.…”
Section: Introductionmentioning
confidence: 99%